Pendampingan Penanaman dan Pemanfaatan Tanaman Obat Keluarga (TOGA) Dalam Program Peningkatan Peranan Wanita menuju Keluarga Sehat Sejahtera (P2WKSS) di Desa Sakerta Timur Kabupaten Kuningan - Marini Marini; Imas Maesaroh; azmi Darotulmutmainnah; Nova Oktavia (Gayaku Publisher, 2023)
In order to improve the degree of public health, one thing that can be done is planting and utilizing TOGA (family medicinal plants). TOGA development can also be used as a flagship program for residents in East Sakerta Village (Saktim) Darma District, Kuningan Regency, in addition to improving health as well as being a superior product to increase the economic value of the community through post-harvest processing. This community service aims to increase the knowledge and abilities of community members, especially members of the tourism awareness group (Pokdarwis) in Saktim Village in the utilization and processing of medicinal plants into more economical drug dosage forms. Community service activities in the Increasing the Role of Women towards a Healthy and Prosperous Family (P2WKSS) program are carried out by providing counseling about the properties of medicinal plants, and training in making TOGA gardens and the process of making traditional medicines.